Long‐term clinical outcomes of periodontal regeneration with enamel matrix derivative: A retrospective cohort study with a mean follow‐up of 10 years. Issue 4 (8th September 2021) - De Ry, Siro P.; Roccuzzo, Andrea; Lang, Niklaus P.; Sculean, Anton; Salvi, Giovanni E.
Abstract: Background: Despite the large body of evidence on the efficacy of enamel matrix derivative (EMD) in the treatment of periodontal intrabony defects, few studies reported long‐term data (≥10‐year). Methods: Periodontal patients treated with regenerative surgery with EMD between 1999 and 2012 were invited to participate in a clinical examination. The following clinical parameters were recorded and compared at baseline (T0), 6 months after surgery (T1) and after at least 8 years of follow‐up (T2): probing depth (PD), gingival recession (GR), clinical attachment level (CAL), plaque and bleeding scores. The primary outcome variable was CAL change. Results: Forty‐one patients with 75 treated teeth were available for analysis. Out of these, 68 (tooth survival rate: 90.7%) reached the latest follow‐up with a mean observation period of 10.3 years (range: 8.0 to 21.3). The most frequent reason for tooth loss was recurrence of periodontal disease. Tooth survival curves showed a statistically significant difference between smokers and non‐smokers ( P = 0.028). Mean CAL changed from 8.43 ± 1.86 (T0) to 6.47 ± 1.70 (T1) ( P < 0.001) and to 5.91 ± 1.83 (T2) ( P < 0.001). At T1, a CAL gain of ≥3 mm was measured in 35% of the defects whereas at T2 it was detected in 51% of cases. Conclusions: Within their limitations, the present results have shown that in intrabony defects, the clinical improvements obtained following regenerative surgery with EMD can be maintained on a mean period of 10 years. Smoking status and maxillary molars were correlated with an increased risk for tooth and CAL loss, respectively.